d Intellectual Resistance as Impetus for Lifelong Learning for Social Justice - Kristopher Wells (Adult Education Research Conference, 2006)
This paper employs critical social learning perspectives to investigate the themes of emotional resilience, intellectual resistance, and lifelong learning evident in the experiences of three gay male young adults whom I situate as activist-educators. I discuss how these young adults integrate emotional labour and social learning into resistance work to create counterpublics, which lay challenge to exclusionary heteronormative educational spaces.
Keywords: Queer; social justice; emotions; lifelong learning; activism